1997
DOI: 10.1597/1545-1569(1997)034<0199:codcfp>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-D Calculations from Periapical and Occlusal Radiographs Versus 3-D Calculations from CAT Scans in Determining Bone Support for Cleft-Adjacent Teeth Following Early Alveolar Bone Grafts

Abstract: Routine dental radiographs were able to estimate the total 3-D bone support for the roots of cleft adjacent teeth as determined by CAT scan to a statistically significant degree when groups where compared. The clinical significance for evaluation of individual cases was less impressive with a wide range of variability and a level of agreement that required acceptance of differences up to 25%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 14 publications
0
18
0
4
Order By: Relevance
“…9,10 This is because 2D radiographs are subject to limitations such as image enlargement, distortion, structural overlap, limited identifiable landmarks, positioning problems and the effects of these on subsequent image quality, resulting in an overestimation of success rates by around 17-25%. 11,12 Alongside developments in 3D imaging, 3D virtual models produced with computeraided design (CAD) software and 3D printing (CAM) hardware have opened up a range of opportunities in education, science, technology, healthcare and industry.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 This is because 2D radiographs are subject to limitations such as image enlargement, distortion, structural overlap, limited identifiable landmarks, positioning problems and the effects of these on subsequent image quality, resulting in an overestimation of success rates by around 17-25%. 11,12 Alongside developments in 3D imaging, 3D virtual models produced with computeraided design (CAD) software and 3D printing (CAM) hardware have opened up a range of opportunities in education, science, technology, healthcare and industry.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenstein et al (1997) investigated the agreement between 3D and 2D assessment and found out that although 2D method can be used in evaluating bone-graft success for a group of UCLP patient, 3D computed tomography is still a superior, and probably the only assessment method for determining the volumetric bone support for cleft-adjacent teeth in certain clinical situations in which great accuracy were called. 16 The present case represented a high success ratio of %84.78 in the fourth year with 3D assessment. Bone loss was found to be in bucco-palatine direction.…”
Section: Discussionmentioning
confidence: 59%
“…Kemik hacmindeki değişiklikleri değerlendirmek için ise mutlaka 3 boyutlu görüntülemelere ihtiyaç duyulmaktadır (4). Bu yüzden bilgisayarlı tomografi (BT) ve KIBT kullanımı giderek yaygınlaşmaktadır (29,30). Bu yöntemlerle elde edilen kesitlerin 3 boyutlu rekonstrüksiyonu ile birlikte karşılaştırmalı analizleri kemik greft hacmi hakkında objektif sonuçlar vermektedir (31 …”
Section: Gereç Ve Yöntemunclassified